Spillover effects in local labor markets: evidence from mass layoffs ; conference paper - Gathmann, Christina; Helm, Ines; Schönberg, Uta (Jahrestagung des Vereins für Socialpolitik 2014, 2014)
Governments are often willing to subsidize firms on the verge of bankruptcy. The main economic rationale behind these interventions is that a plant closure would not only harm the workers employed in that plant, but create a domino effect on the regional economy as a whole. Yet, little is still known empirically how important these spillover effects are for economic development in the region. In this paper, we use administrative data of all workers and firms in Germany to quantify the spillover effects of mass layoffs. For the empirical analysis, we combine a difference-in-differences estimator with an event-study approach. We find sizeable negative spillover effects on the regional economy: regions, and especially firms producing in the same sector as the firm hit by a mass layoff, lose many more jobs than in the initial layoff. In contrast, we find few negative effects for workers employed (but not directly affected by the layoff) in the region. As such, mass layoffs seem to have negative spillovers locally, but not nationally.
Keywords: Graue Literatur; Konferenzschrift